Building of the old Post Office and Telegraph of Lima. History of a built heritage - Barrera Camarena, Henry (2020)
The Central Mail of Lima, or formerly called Correo y Telégrafo de Lima, is a little known heritage, in part because today it is given a variety of uses, added to the fact that the last generations of the population have not come to use this service. The latter is a direct cause of the advancement of technology and the digital age. For these reasons, the objective of this work is to reassess its historical importance and the architectural design that it originally held, which over time has been modified, without this meaning the loss of its value. For this, the use of primary source was used, both in images and in information, which is the basis of this study. The conservation of heritage is a social obligation, from the field of history you can contribute to this noble deed. A monument like this, which has overcome the fluctuations of time, must not only be valued per se, its complexity can contribute to continue knowing the future of the ancient City of Kings.